Filogenia molecular e revisão taxonômica de Senecio Sect. Adamantina Cabrera, Sect. Bahiana D.J.N. Hind e Sect. Paranaia (Asteraceae - Senecioneae) - Fernanda Santos Freitas (2016)
Senecioneae is the largest tribe in Asteraceae with approximately 3,500 species grouped in 150 genera. One-third of its species are placed in the genus Senecio. In Brazil Senecio is represented by 60 species, most of them occurring in the Southern and Southeastern mountains. Senecio is traditionally divided in sections, and in the last revision of Brazilian species it was divided in 15 sections, but currently only 11 sections are recognized as Senecio. Besides the floristic importance and representativity for Brazilian biodiversity, the genus has been receiving little attention. The main reason for it is the hard taxonomy of the genus, caused by the relatively high number of species. Since Senecio is a recognized polyphyletic genus that has significant morphological and taxonomic complexity, a revision of Brazilian species is needed, and a good alternative would be a sectional approach. Senecio sect. Adamantina and S. sect. Paranaia are small sections endemic to Brazil that emerged in previous studies as monophyletic groups, distantly related to Senecio sensu stricto. Given the above, this dissertation proposes phylogenetic hypotheses for Senecio sect. Adamantina, S. sect. Bahiana, and S. sect. Paranaia, to evaluate their monophyly, and the relationships between these sections and their closely related genera. In chapter 1 we expanded the sampling of taxa, using molecular data from DNA sequence from the nuclear (ITS and ETS), and plastids (trnH-psbA and trnL-F) and morphological characters traditionally used in secctional circumscriptions for the genus. It was confirmed that Senecio sects. Adamantina and Paranaia are not closely related to Senecio, these sections are not monophyletic, and they form a clade with some species sympatric, and morphologically related, Dendrophorbium and S. sect. Cacaliastrum. We therefore propose to segregate the species in this clade as a new genus Tomentecio, denominated due to the conspicuous white indument present in the abaxial surface of the leaves of most of the species. We propose the new combinations for the new genus. In chapter II a taxonomic revision of Tomentecio is presented, with descriptions and identification keys for all taxa, taxonomic comments, geographical distribution, and also illustrations. In this revision fourteen species are recognized, one variety is synonymized and seis lectotypes are designated.